miR-132 inhibits lung cancer cell migration and invasion by targeting SOX4 - Li, Yang; Zu, Lingling; Wang, Yuli; Wang, Min; Chen, Peirui; Zhou, Qinghua (Journal of Thoracic Disease, 2015)
Background: Multiple MicroRNAs (miRNAs) have been identified in the development and progression of lung cancer. However, the expression and roles of miR-132 in non-small cell lung cancer (NSCLC) remain largely undefined. The aim of this study is to investigate the biological functions and its molecular mechanisms of miR-132 in human lung cancer cells. Methods: MiR-132 expression was measured in human lung cancer cell lines by quantitative real-time PCR (qRT-PCR). The cells migration and invasion ability were measured by wound healing assay and transwell assay. The influence of miR-132 on tumor progression in vivo was monitored using NSCLC xenografts in nude mice. The target gene of miR-132 was determined by luciferase assay and western blot. Results: The expression level of miR-132 was dramatically decreased in examined lung cancer cell lines. Then, we found that introduction of miR-132 significantly suppressed the migration and invasion of lung cancer cells in vitro. Besides, miR-132 overexpression could also inhibit tumor growth in the nude mice. Further studies indicated that the sex determining region Y-box 4 (SOX4) is a target gene of miR-132. SOX4 re-introduction could reverse the anti-invasion role of miR-132. Conclusions: Our finding provides new insight into the mechanism of NSCLC progression. Therapeutically, miR-132 may serve as a potential target in the treatment of human lung cancer.